2020
DOI: 10.1007/s40333-020-0092-8
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for the sustainable use of water and land resources under a changing climate and increasing salinization in the Jizzakh irrigation zone of Uzbekistan

Abstract: Jizzakh Province in Uzbekistan is one of the largest irrigated areas in Central Asia without natural drainage. In combination with aridity, climate change and extensive irrigation practices, this has led to the widespread salinization of agricultural land. The aim of this study was to identify opportunities to improve the reclamation status of the irrigated area and how best to effectively use the water resources in Jizzakh Province based on investigations conducted between 1995 and 2016. A database of field m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…On the other hand, inappropriate management perspectives on water abstraction, problems related to the management of unauthorized abstractions, the infrastructure, and water allocation scheduling were recognized as problems of water resources management. This is consistent with the findings of Chaudhuri and Roy (2019), Chang (2020), Pešić and Jakovljević (2020), Kulmatov et al (2020), Sahrina et al (2020), and Abd Ellah (2020), who have found that the challenges of management of unauthorized abstractions and an inefficient as well as a carefree water-using attitude and weak infrastructures have been proven to drive the risk and need to take strategic precautions. Furthermore, Haryani (2021) pointed to the challenge of simplifying the adoption of conservation and sustainable use approaches to promoting the implementation of practices in local communities.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, inappropriate management perspectives on water abstraction, problems related to the management of unauthorized abstractions, the infrastructure, and water allocation scheduling were recognized as problems of water resources management. This is consistent with the findings of Chaudhuri and Roy (2019), Chang (2020), Pešić and Jakovljević (2020), Kulmatov et al (2020), Sahrina et al (2020), and Abd Ellah (2020), who have found that the challenges of management of unauthorized abstractions and an inefficient as well as a carefree water-using attitude and weak infrastructures have been proven to drive the risk and need to take strategic precautions. Furthermore, Haryani (2021) pointed to the challenge of simplifying the adoption of conservation and sustainable use approaches to promoting the implementation of practices in local communities.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of reserves, Russia accounts for 20% of the global freshwater resources (excluding glaciers and groundwater). In Russia, in the 1960-80s, a large amount of groundwater was in-depth studied and its reserves amounted to 85 million tons [14,15].…”
Section: Global Groundwater Usementioning
confidence: 99%
“…In many European countries, such as Austria, Belgium, Hungary, Lithuania, Germany, Belarus, Denmark, Romania, Switzerland and the former Yugoslavia, the share of groundwater used for domestic and drinking purposes is more than 70%, while in Bulgaria, France, Italy, the Netherlands, Portugal, Czechia, and Slovakia, this amount is 50-70% [14][15][16]. To pinpoint such countries among them, the groundwater monitoring network in Bulgaria includes 508 monitoring points: 106 springs, 340 deep and shallow wells, and 62 pumping stations.…”
Section: Global Groundwater Usementioning
confidence: 99%
See 1 more Smart Citation
“…The main reason for this is that the slope and closed river-bed basins are located in the central part of the oasis, and they head towards the lake. Such conditions effect for the accumulation of salts in the slope and AALS, as well as, increase mineralization of lake water (Kulmatov,et al, 2013;Kulmatov, et al, 2020). With the rising of lake water level, the groundwater level in the surrounding landscapes and secondary salinization in the soil will also increase (Wahyuni et al, 2009;Kulmatov, et al, 2021).…”
Section: Soil Salinity Condition In Agroirrigation Landscapesmentioning
confidence: 99%